# Difference between revisions of "Delta derivative of reciprocal of classical polynomial"

From timescalewiki

(Created page with "==Theorem== Let $\mathbb{T}$ be a time scale, let $\alpha$ a constant, let $m \in \mathbb{N}$, and define $g\colon \mathbb{T} \rightarrow \mathbb{R}$ by $g(t)=\dfrac{1}{(t...") |
|||

Line 7: | Line 7: | ||

==References== | ==References== | ||

* {{BookReference|Dynamic Equations on Time Scales|2001|Martin Bohner|author2=Allan Peterson|prev=Delta derivative of classical polynomial|next=findme}}: Theorem 1.24(ii) | * {{BookReference|Dynamic Equations on Time Scales|2001|Martin Bohner|author2=Allan Peterson|prev=Delta derivative of classical polynomial|next=findme}}: Theorem 1.24(ii) | ||

+ | |||

+ | [[Category:Theorem]] | ||

+ | [[Category:Unproven]] |

## Revision as of 06:03, 10 June 2016

## Theorem

Let $\mathbb{T}$ be a time scale, let $\alpha$ a constant, let $m \in \mathbb{N}$, and define $g\colon \mathbb{T} \rightarrow \mathbb{R}$ by $g(t)=\dfrac{1}{(t-\alpha)^m}$. Then $$g^{\Delta}(t)=-\displaystyle\sum_{j=0}^{m-1} \dfrac{1}{(\sigma(t)-\alpha)^{m-j}(t-\alpha)^{j+1}},$$ where $\sigma$ denotes the forward jump.

## Proof

## References

- Martin Bohner and Allan Peterson:
*Dynamic Equations on Time Scales*(2001)... (previous)... (next): Theorem 1.24(ii)